The timing of adoption of cleaner technologies: Private costs and public incentives - Cesare Dosi; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2000)
Spontaneous adoption of cleaner technologies can be slowed down by various sources of inertia. Investment irreversibility, uncertainty about the actual private benefits, and the expectation of declining adoption costs due to the diffusion of environmental innovation, may involve a timing of technological migration incompatible with avoidance of excessive pollutant accumulation. In this paper we examine the implications of the sources of inertia on the design of public incentives aimed at accelerating abandonment of polluting technologies when the policy-maker faces incomplete information about the private switching costs.
Keywords: Q28; O38; 330; Environmental policy; technological change; irreversibility; network externalities; public incentives; Umweltpolitik; Anreizregulierung; Umwelttechnik; Umweltmanagement; Theorie